Fractional Calculus in Modelling of Measuring Transducers - Luft, M.; Cioc, R.; Pietruszczak, D. (Elektronika ir Elektrotechnika, 2011)
The paper is inspired by developments of fractional calculus in areas of control theory and electrical measurements. It outlines an example of modelling the measuring transducers with the use of this calculus. The algorithm determining these models is presented in the form of a fractional calculus notation and then the models are compared to the ones described by means of classical differential equations. Tests are executed in the Matlab/Simulink programme. Ill. 6, bibl. 7 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.297